Utilizing nature's endowment: artificial leaf concept for methane activation to C-C coupled ethanol or ethylene - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Avani, Mangaladasan J.; Bajpai, Himanshu; Salgaonkar, Kranti N.; Javaregowda, Bharathkumar H.; Gopinath, Chinnakonda S. (Sustainable Energy & Fuels, 2025)
Methane activation (MA) to platform chemicals under ambient conditions still remains an open challenge to be fully realised. The present work shows the fabrication of CeVO4 quantum dots (CV-QDs) by a bottom-up approach; they are assembled from Ce3+ and metavanadate ions, and structurally and electronically integrated into the micro-/meso-pores of TiO2 (CV-QD-TiO2 (CVT)), demonstrating the conversion of MA to ethanol/ethylene by visible light-driven photocatalysis. CV-QDs in confined pores modify the quantum confinement effects and are characterized by physicochemical methods. The current synthetic strategy is potentially scalable and results in sub-quadrillion heterojunctions in a 1 mg CVT photoanode spread over 1 cm2. MA with CVT under one-sun conditions demonstrates similar to 100% selectivity to ethanol, yielding 4.36 mu mol h-1 cm-2, with a solar-to-fuel efficiency (STFE) of 0.56. Further, by employing a co-catalyst, significant STFE (5.08) and yield (39.5 mu mol h-1 cm-2) are achieved selectively towards ethylene. A deliberate addition of methanol increases the rate of ethanol production by 17.2 times, indicating that the methyl-methoxy interaction is the origin of C-C coupling. Weight is normalized to a gram of CV-QDs in a large area CVT photoanode to yield 109 mmol h-1 gCV-QD-1 of ethanol and 988 mmol h-1 gCV-QD-1 of ethylene. Enhanced activity and selectivity towards the C2-product is attributed to band-edge modulation and trillions of heterojunctions, which in turn facilitate charge separation and charge transfer for effective charge utilisation at redox sites.